Meningkatkan Literasi Keuangan Siswa SMA melalui Simulasi Trading dan Kuis Interaktif - Wongso, Enrico; Susanto, Leonardo Christian; Ferdian, Edric; Anastasia, Njo (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2026)
This community service activity was conducted to improve the financial literacy of high school students through an experiential learning method. The main issue addressed was the low level of students’ understanding of money management, saving, and investment. The activity was carried out in two batches and involved 35 students from several schools. Students received financial literacy materials, participated in virtual stock trading simulations, and engaged in interactive quizzes. Evaluation was conducted by comparing pre-test and post-test results. The findings showed a significant improvement in students’ understanding of financial management, awareness of the importance of saving, and comprehension of investment risks. The experiential learning approach proved to be effective as students learned directly through practice. This activity provided not only theoretical knowledge but also enjoyable practical experience, helping students to develop responsible financial thinking from an early age